Kajian keberhasilan pascatambang pertambangan emas (au) PT. Kelian equatorial mining (kem) Di Kabupaten Kutai Barat Propinsi Kalimantan Timur (Jurnal Geologi Pertambangan (JGP), 2020)
AbstractMining activities have positive impacts but can also cause negative impacts in the form of fundamental changes in a number of environmental components if not managed properly. The post-mining program aims to restore or improve the condition of the remaining resources of mining activities so that they can be used as much as possible for the purpose of post-mining sustainable development. So that the criteria for post-mining success can be reached. This research uses descriptive analysis method, this method is carried out by describing the facts which are then followed by analysis and providing sufficient understanding and explanation. Data collection techniques using primary data are data taken directly through the process of field observations, in this case the primary data taken includes data on: (1) Activity flow diagrams (2) Protected Forest Monitoring (3) Questionnaires. Mining success depends on several things such as: mine closure preparation, environmental maintenance and environmental monitoring. Keywords: post-mining, reclamation, environmental monitoring.